Spontaneous Coronary Artery Dissection in the Gulf: G-SCAD Registry. (January 2021) - Daoulah, Amin; Al-Faifi, Salem M.; Alhamid, Sameer; Youssef, Ali A.; Alshehri, Mohammed; Al-Murayeh, Mushabab; Farghali, Tarek; Maghrabi, Mohamed; Balghith, Mohammed; ElSayed, Osama; Alasmari, Abdulaziz; Arafat, Amr A.; et al.
Data on spontaneous coronary artery dissection (SCAD) is based on European and North American registries. We assessed the prevalence, epidemiology, and outcomes of patients presenting with SCAD in Arab Gulf countries. Patients (n = 83) were diagnosed with SCAD based on angiographic and intravascular imaging whenever available. Thirty centers in 4 Arab Gulf countries (Kingdom of Saudi Arabia, United Arab Emirates, Kuwait, and Bahrain) were involved from January 2011 to December 2017. In-hospital (myocardial infarction [MI], percutaneous coronary intervention, ventricular tachycardia/fibrillation, cardiogenic shock, death, implantable cardioverter-defibrillator placement, dissection extension) and follow-up (MI, de novo SCAD, death, spontaneous superior mesenteric artery dissection) cardiac events were recorded. Median age was 44 (37-55) years, 42 (51%) were females and 28.5% were pregnancy-associated (21.4% were multiparous). Of the patients, 47% presented with non-ST-elevation acute coronary syndrome, 49% with acute ST-elevation myocardial infarction, 12% had left main involvement, 43% left anterior descending, 21.7% right coronary, 9.6% left circumflex, and 9.6% multivessel; 52% of the SCAD were type 1, 42% type 2, 3.6% type 3, and 2.4% multitype; 40% managed medically, 53% underwent percutaneous coronary intervention, 7% underwent coronary artery bypass grafting. Females were more likely than males to experience overall (in-hospital and follow-up) adverse cardiovascular events ( P = .029).